1-Deoxysphingolipids, Early Predictors of Type 2 Diabetes, Compromise the Functionality of Skeletal Myoblasts - Tran, Duyen; Myers, Stephen; McGowan, Courtney; Henstridge, Darren; Eri, Rajaraman; Sonda, Sabrina; Caruso, Vanni (Frontiers in Endocrinology, 2021)
Metabolic dysfunction, dysregulated differentiation, and atrophy of skeletal muscle occur as part of a cluster of abnormalities associated with the development of Type 2 diabetes mellitus (T2DM). Recent interest has turned to the attention of the role of 1-deoxysphingolipids (1-DSL), atypical class of sphingolipids which are found significantly elevated in patients diagnosed with T2DM but also in the asymptomatic population who later develop T2DM. In vitro studies demonstrated that 1-DSL have cytotoxic properties and compromise the secretion of insulin from pancreatic beta cells. However, the role of 1-DSL on the functionality of skeletal muscle cells in the pathophysiology of T2DM still remains unclear. This study aimed to investigate whether 1-DSL are cytotoxic and disrupt the cellular processes of skeletal muscle precursors (myoblasts) and differentiated cells (myotubes) by performing a battery of in vitro assays including cell viability adenosine triphosphate assay, migration assay, myoblast fusion assay, glucose uptake assay, and immunocytochemistry. Our results demonstrated that 1-DSL significantly reduced the viability of myoblasts in a concentration and time-dependent manner, and induced apoptosis as well as cellular necrosis. Importantly, myoblasts were more sensitive to the cytotoxic effects induced by 1-DSL rather than by saturated fatty acids, such as palmitate, which are critical mediators of skeletal muscle dysfunction in T2DM. Additionally, 1-DSL significantly reduced the migration ability of myoblasts and the differentiation process of myoblasts into myotubes. 1-DSL also triggered autophagy in myoblasts and significantly reduced insulin-stimulated glucose uptake in myotubes. These findings demonstrate that 1-DSL directly compromise the functionality of skeletal muscle cells and suggest that increased levels of 1-DSL observed during the development of T2DM are likely to contribute to the pathophysiology of muscle dysfunction detected in this disease.